Evaluation of gliovascular functions of AQP4 readthrough isoforms - Mueller, Shayna M.; McFarland White, Kelli; Fass, Stuart B.; Chen, Siyu; Shi, Zhan; Ge, Xia; Engelbach, John A.; Gaines, Seana H.; Bice, Annie R.; Vasek, Michael J.; Garbow, Joel R.; Culver, Joseph P.; et al. (Frontiers in Cellular Neuroscience, 2023)
Aquaporin-4 (AQP4) is a water channel protein that links astrocytic endfeet to the blood-brain barrier (BBB) and regulates water and potassium homeostasis in the brain, as well as the glymphatic clearance of waste products that would otherwise potentiate neurological diseases. Recently, translational readthrough was shown to generate a C-terminally extended variant of AQP4, known as AQP4x, that preferentially localizes around the BBB through interaction with the scaffolding protein α-syntrophin, and loss of AQP4x disrupts waste clearance from the brain. To investigate the function of AQP4x, we generated a novel AQP4 mouse line (AllX) to increase relative levels of the readthrough variant above the ~15% of AQP4 in the brain of wildtype (WT) mice. We validated the line and assessed characteristics that are affected by the presence of AQP4x, including AQP4 and α-syntrophin localization, integrity of the BBB, and neurovascular coupling. We compared AllXHom and AllXHet mice to wildtype, and to previously characterized AQP4 NoXHet and NoXHom mice, which cannot produce AQP4x. Increased dose of AQP4x enhanced perivascular localization of α-syntrophin and AQP4, while total protein expression of the two were unchanged. However, at 100% readthrough, AQP4x localization and formation of higher-order complexes was disrupted. Electron microscopy showed that overall blood vessel morphology was unchanged except for increased proportion of endothelial cells with budding vesicles in NoXHom mice, which may correspond to a leakier BBB or altered efflux that was identified in NoX mice using MRI. These data demonstrate that AQP4x plays a small but measurable role in maintaining BBB integrity as well as recruiting structural and functional support proteins to the blood vessel. This also establishes a new set of genetic tools for quantitatively modulating AQP4x levels.